Beban Kognitif Siswa Pada Materi Pencemaran Lingkungan Berbantuan Prezi Application: (Student Cognitive Load on Environmental Pollution Material Assisted by Prezi Application) - Eka Lesmana Sari; Billyardi Ramdhan; Sistiana Windyariani (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
Cognitive load theory is a theory used to study the limitations of working memory in receiving and processing new information obtained by students, mental efforts owned by students and student learning outcomes after studying the learning that has been presented. The purpose of this study was to determine the cognitive load profile of students of class VII Junior High School Sukabumi on environmental pollution material with the help of prezi application. Qualitative descriptive research method with research subjects as many as 40 students. The instrument uses description questions, questionnaires, and multiple choice questions. The results of the study describe that the cognitive load profile of students' intellectual cognitive load (ICL) in receiving and processing information has a fairly high average value of 81.25. This shows that the cognitive load profile of students is low, then the results described from the extraneous cognitive load (ECL) in the mental efforts of students get an average value of 65.2. This illustrates that there is a cognitive load profile that is owned by students and finally the learning outcomes using germane cognitive load (GCL), where students get an average score of 63, this is the same as ECL which describes students as having a cognitive load profile because of the low value of learning outcomes. obtained by students. Abstrak.Teori beban kognitif merupakan teori yang digunakan untuk mempelajari keterbatasan memori kerja dalam menerima dan mengolah informasi baru yang diperoleh peserta didik, usaha mental yang dimiliki oleh peserta didik dan hasil belajar peserta didik setelah mempelajari pembelajaran yang sudah disampikan. Tujuan Penelitian ini untuk mengetahui profil beban kognitif peserta didik kelas VII Sekolah Menengah Pertama Negeri Kota Sukabumi pada materi pencemaran lingkungan dengan berbantuan prezi application. Metode penelitian deskriptif kualitatif dengan subyek penelitian sebanyak 40 orang peserta didik. Instrumen menggunkan soal uraian, kuisioner, dan soal pilihan ganda. Hasil penelitian mendeskripsikan bahwa profil beban kognitif siswa instrisic cognitive load (ICL) dalam menerima dan mengolah informasi memiliki nilai rata-rata yang cukup tinggi yaitu 81,25. Hal tersebut menunjukkan profil beban kognitif yang dimiliki peserta didik rendah, kemudian hasil yang digambarkan dari extraneous cognitive load (ECL) dalam usaha mental peserta didik memperoleh nilai rata-trata 65,2. Hal tersebut menggambarkan terdapat profil beban kognitif yang dimiliki oleh siswa dan yang terakhir hasil belajar dengan menggunakan germane cognitive load (GCL) yaitu siswa memperoleh nilai rata-rata 63 hal tersebut sama dengan ECL yang menggambarkan peserta didik memiliki profil beban kognitif karena rendahnya nilai hasil belajar yang diperoleh peserta didik.